Mempertahankan Tradisi “A Glenon” Di Tengah Masyarakat Desa Daleman Sampang Madura - .Alfin Hadi, Moch (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
This research is a qualitative researchthat aims to describe how the "A Glenon" tradition survives in the society of Daleman Village. A Glenon itself is a Madurese tradition where when passing a person or group, whether riding or not, walking with "andhep ashor" (bowing slightly forward) accompanied by the words "Glenon" which means excuse me. Now the tradition or practice can be abbreviated as A Glenon. Informants in this study used a purposive sampling technique, namely the technique of determining informants based on certain criteria or considerations. The selection of informants in this study is based on the first criterion, namely that the informant must be a local community leader who becomes a reference in terms of society. The research interview was conducted without coercion by means of the user having to state his willingness to be an informant. The researcher added ordinary residents as supporting informants in this study. The results of this study indicate that the Daleman village community still maintains the "A Glenon" tradition with several factors including the role of "Oreng Seppo" which is a reference for traditional or cultural issues. Also very influential is the role of the kiai, both pesantren kiai and kiraan kiai, who continue to give messages to keep applying the moral values of al-karimah, one of which can be realized by practicing A Glenon. However, there are also things that can cause the decadence of this tradition, namely the individualist attitude due to the swift currents of globalization and information and the growth of a new phenomenon called social media.